Morphological and pathological variations in Peronospora parasitica infecting Brassica species - G.S. SAHARAN, NARESH MEHTA and (Indian Phytopathology, 2002)
The host range of 9 isolates of downy mildew fungus, Peronospora parasitica collected from the leaves and stagheads of Toria, Yellow Sarson, Brown Sarson, Raya, cauliflower and B. nigra (Rai) was assessed on a set of 17 host differentials. The results showed that isolates from oil yielding Brassicas infected all differentials, except B. aLba, whereas, the isolate obtained from cauliflower leaf did not infect B. ea rina ta, B. alba, B. nigra, B. chinensis, B. pekinensis and B. napus. There were no significant differences among the conidial size of the isolates collected from leaves and stagheads. However, there were significant differences between each group. Conidia from different isolates did not show differences in germination. However, on the basis of pathogenecity, the isolates were classified into two distinct pathotypes, one from cauliflower and other from oil yielding Brassicas.